Beyond textuality in Islamic legal exegesis: intertextuality and hypertextuality for codifying legal maxims of Islamic criminal law - Zakariyah, Luqman (Association of Muslim Social Scientists, 2014)

(untitled)
When studying textuality in the codification1 of Islamic legal maxims (qawā‘id fiqhīyah), it is worth researching how intertextuality and hypertextuality can be used as linguistic mechanisms to help understand Qur’anic texts and how such texts cohere to form legal maxims in Islamic criminal law. An in-depth study of medieval Qur’anic exegetes reveals the length to which Muslim scholars have gone to link texts to extract contextual meanings from the Qur’an and, perhaps, to codify Islamic legal maxims. Two such approaches are intertextuality and hypertextuality.